Extraction and chromatographic analysis of the Nematicide Cadusafos - Cotta, Aloísio JB; Pereira, Mariana de Martin; Santos, Mellina Dasmaceno Rachid; Gomes, Emanuelle G.; Campos, Débora de J.; Silva, Marcelo Barreto da (Brazilian Journal of Production Engineering, 2020)
In agriculture, the use of nematicides is a common practice as a corrective measure for crop protection, since the infestation of soils and roots by phytonematoids can cause great damage. Cadusafós (active ingredient of Rugby 200 CS) is one of the main pesticides used to control nematodes. The present work aimed to develop an extraction and analysis method for the Cadusafós, in soil samples, using the gas chromatography technique coupled to mass spectrometry (CG-MS), for quantification. The extraction efficiency of different solvents (dichloromethane (DCM), hexane (HEX), acetonitrile (ACN) and ethyl acetate (AcEt)) was tested, as well as the effect of adding NaCl during the extraction, in order to identify the best conditions for sample preparation. The preparation procedures for the doped samples (with Rugby 200 CS), fortified (with Cadusafós analytical standard), in two levels of concentration, extraction, as well as the calibration and instrumental determination in the CG-MS (Shimadzu QP2010) were studied. In the tests performed, it was found that the AcEt is efficient for extracting Cadusafós from the samples. Two soils and doped or fortified portions were analyzed to evaluate the performance of the method, which showed satisfactory recovery and precision (<10%), without the need for a cleanup step before the chromatographic determination.